The Development of Health Criminal Law in The Perspective of Dignified Justice: What and How? - I Made Wirya Darma (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Health criminal law in Indonesia has developed significantly since the colonial era until now, marked by the birth of various laws and regulations governing criminal aspects in the health sector. This research aims to analyze the development of health criminal law in Indonesia from the perspective of dignified justice, as well as identify challenges and formulate efforts needed in developing health criminal law in line with the principles of dignified justice. This research uses a normative legal research method with a statutory and conceptual approach, examining primary, secondary, and tertiary legal materials through literature studies. Data analysis was conducted qualitatively with a descriptive-analytical approach, involving the process of data reduction, data presentation, and conclusion drawing. The results of the study explain that the development of health criminal law in Indonesia shows a significant evolution, from limited arrangements in the Criminal Code of colonial heritage to comprehensive laws such as Law No. 36/2009 on Health. The perspective of dignified justice is reflected in efforts to balance the protection of patient rights, the professionalism of health workers, and the interests of society. Although there has been progress, there are still challenges such as the application of the ultimum remedium principle, the balance of rights protection, and adaptation to the development of health technology. Efforts to develop health criminal law in line with the principles of dignified justice require a thorough evaluation of criminal provisions, capacity building of law enforcement officers, development of regulations that are sensitive to the diversity of health practices, and collaboration between stakeholders to deal with the complexity of contemporary health issues.